(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2022)
To overcome the high water content in numerous oil fields, axial inlet hydrocyclone is considered an alternative device of oil-water separation technique that is used downfield. This type of hydrocyclone has a rare previous work compared to other vortex tube separators. Additionally, the accurate mechanism of the enhanced separation process by optimizing the separation technologies remains unclear. Therefore, an extensive study was conducted to expand the application range of the axial inlet hydrocyclone. This workpresents a literature review of the different separation technologies for the axial inlethydrocyclone. These are categorized into two groups: (i) geometrical parameters including, internal swirl element (ISE), swirl chamber, and (ii) operational parameters including, inlet flow rate, feed temperature, mixture fraction, and droplet size. The influence of these parameters on the velocity components profile and pressure drop were analyzed based on the separation performance parameters such as separation efficiency and pressure drop. This work could serve as an engineering tool that results in the enhanced economic workability of separation by hydrocyclone.